(untitled) (London Journal of Research In Science: Natural and Formal, 2025)
This study investigates the biodiversity of urban flora in the arid zone of Bukhara, Republic of Uzbekistan. The research is based on newly proposed methodsexamining the complexity and potential of flora biodiversity. Additionally, the study employs the biodiversity index, which includes species abundance equalization (the probability of species occurrence) and the Shannon index. This work represents the first attempt to calculate biodiversity complexity and potential indicators for real ecological systems. The findings indicate that the biodiversity of Bukhara’s urban flora is characterized by uneven species abundance. A few tree species (Pinus brutia var. eldarica (Medw.) Silba; Ulmus parvifolia L.; Platycladus orientalis (L.) Franco), shrub species (Rosa chinensis Jacq.; Yucca filamentosa L.), and herbaceous species (Cynodon dactylon L.; Salsola sp.; Coreopsis lanceolata L.; Lolium perenne L.; Setaria viridis (L.) P. Beauv) exhibit significant dominance. The study reveals a high level of complexity but a low potential in the structure of urban flora biodiversity, indicating weak resilience, adaptation, and regeneration capability. These results suggest that the fundamental principles governing natural biodiversity transformationslack of identity, unified logic, harmony, purpose, and orderare disrupted within urban ecosystems due to the introduction of subjective logic, harmony, goal orientation, and order.